Relationship between the osteopenic syndrome and coronary artery disease in male patients with ischemic heart disease - Tat’yana Alekseyevna Raskina; E B Malyuta; O L Barbarash; A N Kokov; V L Masenko; V A Voronkina (Современная ревматология, 2014)
Objective. To examine the relationships between measures of bone mineral density (BMD), coronary atherosclerosis, and coronary artery calcification among men with ischemic heart disease (IHD).Materials and Methods. Seventy-four men with angiographically documented IHD were assessed. BMD was measured by dual-energy absorptiometry and defining the T-score, radiopaque selective coronary angiography with the analysis of severity of coronary artery lesions using the SYNTAX score, evaluating the coronary artery calcium score according to the Agatston method. Depending on the T-score, patients were divided into 2 groups: group I – patients with osteopenic syndrome (53 patients) aged 59 (52;68) years; group II – patients with normal BMD (21 patients) aged 58 (54;66 ) years.Results. Osteopenic syndrome among men with IHD was revealed in 71.6% of cases. Severe coronary lesions predominated among patients with osteopenic syndrome (p=0.041). Single-vessel coronary lesions in the group with osteopenic syndrome was detected less frequently than in the normal BMD (p=0.023) group. Calcium score values significantly correlated with the severity of coronary lesions according to the Syntax scale (r=0,53; p=0.002).Conclusion. Reduced bone mineral density among men is associated with hemodynamically significant lesion and correlates with the severity of coronary atherosclerosis, which confirms the likelihood of common pathogenesis of osteopenic syndrome and coronary artery atherosclerosis.